Nonconvulsive Seizures in Critically Ill Children - J Gordon Millichap (Pediatric Neurology Briefs)
All patients <18 years admitted to the ICU at Columbia University Medical Center, New York, between June 1, 2000 and April 30, 2004, and considered critically ill, regardless of etiology, underwent continuous EEG (cEEG) for detection of nonconvulsive seizures (NCSz) in the evaluation of unexplained diminished consciousness.